Exploring the depths of second language processing with eye tracking: An introduction. (July 2020) - Godfroid, Aline; Winke, Paula; Conklin, Kathy
In this paper, we review how eye tracking, which offers millisecond-precise information about how language learners orient their visual attention, can be used to investigate a variety of processes involved in the multifaceted endeavor of second language acquisition (SLA). In particular, we review the last 15 years of research in SLA, in which applied linguists have exploited the information gleaned from eye-tracking metrics to advance the field. As we explain, eye-tracking researchers within SLA have diversified which aspects of SLA they investigate and are entering new territory by pairing eye-tracking metrics with other data-collection methods for data-triangulation purposes. Eye tracking in SLA is also an inherently interdisciplinary endeavor, for which research partnerships with computer scientists hold special promise in the areas of automated language assessment and the evaluation of cognitive functioning and processing. We describe how the papers in this special issue on eye tracking in Second Language Research push the boundaries by: (a) ensuring greater standardization of how eye tracking is used in SLA (Godfroid and Hui, 2020); (b) embedding eye-tracking metrics within a mixed-methods design for more valid and complete data interpretation (Andringa, 2020; Michel et al., 2020); (c) using eye trackers to investigate the nuanced differences in cognitive processes involved across multimodal input and feedback types in SLA (Conklin et al., 2020; McDonough et al., 2020).